Ski-binding loads generated during alpine skiing and alpine touring skiing: A comparison of the retention requirements - Campbell, J.; Scher, I.; Stepan, L.; Campbell, K.; Nichol, J.; Ching, R. (Science and Skiing VII, 2018)
Releasable ski bindings were developed with two primary functions: retention (i.e., holding the ski boot to the ski to allow skiers to maneuver downhill while loads transmitted from the ski to the lower leg remain below the injury threshold) and release (i.e., releasing the ski from the boot when the odds of a lower-leg injury are high, in either twisting or in bending). In the early 1970s, field trials were performed to determine empirically what minimum release requirements (MRR) were sufficient to avoid an inadvertent release of the binding, and those values were then correlated with skier parameters (Shealy, 1982). Skier weight was found to be the best predictor for determining an appropriate release torque value for the MRR and resulted in predicted release values 15-20% lower than other methods (Shealy, 1980). Crawford (1997) later found that the MRR for a given skier was well correlated to skier weight and leg length, but not skier ability. The MRR method was eventually adopted in ISO 8061 as the recommended lower limit for release torque values. Since the standardization of releasable ski bindings and their settings, tibia fractures have decreased by 83% and since the early 1990s have remained relatively stable, accounting for less than 1% of overall injuries (Ettlinger, 2007; Natri, 1999; Johnson, 2009). Alpine touring (AT) is a discipline of skiing in which the skier uses skis to ascend and descend snow-covered terrain in the backcountry. Some AT ski boots use metal fittings to interface with tech bindings. The interface geometry of the inserts and the toe piece of the bindings is not standardized and may produce inadvertent releases. Many users elect to lock out the toe-release mechanism—against the manufacturer`s recommendations—to prevent inadvertent releases. To provide guidance for improving tech binding retention and release, the force transmission path needs to be examined since it may not be the same as for alpine ski bindings. The purpose of this study was to compare the measured MRRs for alpine and AT skiing with the MRRs recommended by international standards for alpine skiing.